Odpowiedzi

2010-03-01T15:24:11+01:00
Musisz pamiętać, że - i - daje +, + i - daje -, + i + daje +
więc:

-8+(-12)-(-6)= -20 + 6 = -14
16+(-17)-(-22)+(-5)-1= -1 - (-27) -1= 25
12-(-6)+(-18)-(-3)= 18 + (-15)= 3
-4+(-7)-(4)-3= -13 - 7= -20
-7-9+(-6)-(-9)= -16 - 6 + 9 = - 16 + 3= -13
2010-03-01T15:25:32+01:00
-8+(-12)-(-6)=-8+(-18)=-26
16+(-17)-(-22)+(-5)-1=-1+-27+-1=-29
12-(-6)+(-18)-(-3)=18+(-15)=3
-4+(-7)-(4)-3=-11-1=-12
-7-9+(-6)-(-9)=-16+3=-13
2010-03-01T15:29:02+01:00
1. -8+(-12)-(-6) = -8-12+6 = -14
2. 16+(-17)-(-22)+(-5)-1 = 16-17+22-5-1 = 15
3. 12-(-6)+(-18)-(-3) = 12+6-18+3 = 3
4. -4+(-7)-(4)-3 = -4-7-7 = -18
5. -7-9+(-6)-(-9) = -7-9-6+9 = -13